In prostate cancer, low adiponectin levels are not associated with insulin resistance. (24th April 2015) - Michalakis, Konstantinos; Venihaki, Maria; Mantzoros, Christos; Vazaiou, Andriani; Ilias, Ioannis; Gryparis, Alexandros; Margioris, Andrew N.
Abstract Purpose Adiponectin, an adipose tissue‐derived hormone with insulin‐sensitizing effect, has been inversely associated with several hormonally dependent malignancies. Prostate cancer is associated with low levels of adiponectin, which have been proposed as an independent risk factor for this malignancy. Aim of this study was to examine whether hypoadiponectinaemia in prostate is associated with insulin resistance. Experimental Design Plasma samples and covariate data in the context of a case–control study of 300 Greek men were evaluated including 75 patients with prostate cancer, 75 patients with benign prostatic hyperplasia (BPH) and 150 age‐matched healthy controls. Results Patients with prostate cancer had significantly lower plasma adiponectin levels compared with the other two groups, that is BPH patients and healthy controls (7·4 ± 5 ng/mL vs. 11·5 ± 6·4 ng/mL and 12·8 ± 8 ng/mL, respectively). On the other hand, no statistically significant differences were found between patients with prostate cancer and the other two groups for both HOMA‐IR and QUICKI (P‐value = 0·551). As expected, in all three groups, the levels of adiponectin correlated negatively with HOMA‐IR (rho = −0·214, P‐value = 0·006), QUICKI (rho = 0·214, P‐value = 0·006) and insulin levels (rho = 0·942, P‐value<0·001). Conclusion In spite of what would have been expected from the relevant literature, our data suggest that the hypoadiponectinaemia in prostatic cancer does not appear to be associated with insulin resistance.